Role of English in Globalization and Multiculturalism with Special Reference to Indian Context: The Role of English Language in Promoting Globalization and Multiculturalism: A Study of Indian Context (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Without language human being cannot live a peaceful life in today’s world. Language plays a great role in the mental, emotional and social development of a person. Among all creations, man alone is endowed with the power of speech. Human language is dynamic, infinite in variety and organic in nature which promotes and sustains social interaction and contributes to the progress of civilization. And this progress of civilization has given birth to globalization. In a multilingual country like, India it is very important to give equal importance to all languages. But with the passing of time the effect globalization has been found in English language especially. The fact is that in India, though English is not our native language but it is the most widely spoken language in the globe. This language gas also affected the field of multiculturalism. Thus to find out the role of English in today’s global as well as multicultural India, the researcher has designed the study with the following objectivesObjectives of the study(i)To study the importance of globalization in today’s world(ii)To study out the impact of globalization on higher education(iii)To study the relationship between globalization and multiculturalismMethodology of the studyTo work on the aforesaid objectives, the researcher has adopted the documentary analysis method.Major findings of the studyIn the present study, the researcher has adopted the documentary analysis method and interpreted the data in the light of hisher own experience. After analyzing and interpreting the data, the researcher has found out the following findings(i)Globalization is of great importance in today’s world. To lead life in a global world, we need to develop a competitive mind and that could be done by taking part in globalization process(ii)Globalization and English are the two sides of the same coins. No one can enjoy globalization without a basic knowledge of English. On the other hand due to globalization the importance of English has been raised not only in India but it the world.(iii)Globalization and multiculturalism are also inter-related. Due to globalization, multiculturalism has got its fullest benefits. That means globalization has opened the path easy to the tourists to get well acquainted with the various cultures and to enrich their own culture. In doing so the knowledge of English is a must.To sum up it can be said that globalization and multiculturalism are inter-related. And their relationship is strengthened by using the very language English. This is because though English is not our native language but it is a national and international link language. So to get the benefit of globalization, it is essential to enrich the field of English teaching in the country.